Manganese superoxide dismutase- cell-penetrating peptide fusion protein supplementation as a novel strategy for the effective cryopreservation of Portuguese oyster Crassostrea angulata oocytes - Cheng, Chiu-Min; Nagarajan, Dillirani; You, Wen-Jie; Pan, Yi-Ting; Dong, Cheng-Di (Aquaculture, 2025)
Portuguese oyster Crassostrea angulata is an economically crucial cultured shellfish in Taiwan. While sperms and embryos of oysters can be preserved by freezing with considerable success, oocyte cryopreservation is challenging due to unique oocyte morphological features, freeze-thaw process induced oxidative stress, and cellular damage resulting in poor survival, low fertilization rate, and increased larval mortality. Oyster oocyte cryopreservation techniques have yet to be explored. In this study, the antioxidant enzyme superoxide dismutase (SOD) was evaluated as a cryoprotectant additive to alleviate oxidative stress during cryopreservation in Portuguese oyster oocytes. Three different recombinant manganese superoxide dismutase (MnSOD) fused with cell-penetrating peptide TAT, namely TAT-MnSOD, MnSOD, and MnSOD-TAT, were constructed. The purified recombinant proteins with TAT fusion could be internalized by oyster oocytes, as confirmed by western blot analysis. TAT fusion reduced 25–39 % of MnSOD activity, and the N-terminus fusion of the TAT peptide was more effective in cell internalization than the C-terminus fusion. Oyster oocytes were subject to cryopreservation with 10 % DMSO as a base cryoprotectant and 5 μM concentration of the purified recombinant MnSOD proteins. TAT-MnSOD attained the highest survival rate (74.5 ± 2.0 %) and fertilization rate (76 ± 7.4 %) in post-thaw oocytes, 2.6-fold and 3.8-fold higher than the base cryoprotectant group. These results indicated that cell-penetrating antioxidant enzyme supplementation in the cryoprotectant solution could significantly improve oocyte survival and fertilization rates of Portuguese oyster oocytes. TAT-MnSOD is a suitable additive for the cryopreservation of shellfish oocytes. [Display omitted] •Superoxide dismutase supplementation addresses oxidative stress during cryopreservation of Portuguese oyster Crassostrea angulata oocytes.•Fusion of cell-penetrating peptide facilitated MnSOD internalization in oocytes.•TAT-MnSOD supplementation improved post-thaw oocyte survival rate by 2.6-fold compared to DMSO alone.•TAT-MnSOD supplementation improved post-thaw oocyte fertilization rate by 4.1-fold compared to DMSO alone.